Using of the ROOT package for physical data processing - Prokhorets, I.M.; Prokhorets, S.I.; Rudychev, Y.V.; Khazhmuradov, M.A. (Вопросы атомной науки и техники, 2009)
ROOT is object-oriented framework, which is actively developed in CERN now. In this article potential of ROOT using for more effective analysis of the data from mathematical modeling and physics experiments are considered.